THOUGHT AND FEELINGS IN OYBEK'S POETRY OF LAST YEARS TO CHAIR PROPORTION - Salimova, Dilnavoz (Social science and innovation, 2024)
The poem has an important place in social life not only in the form and content of the thought and the feeling associated with it, but also in the information it contains. "Creative imagination is not enough to truly enjoy reading a poem. Because a poem is a speech that is happening all the time, it is not a simple string of words. Because the words in it are the way to the melody that has spread from the poet's heartstrings.